2017
DOI: 10.21037/jtd.2017.07.82
|View full text |Cite
|
Sign up to set email alerts
|

Donors after cardiocirculatory death and lung transplantation

Abstract: Abstract:The number of patients actively awaiting lung transplantation (LTx) is more than the number of suitable donor lungs. The percentage of lung retrieval rate is lower when compared to other solid organs.The use of lungs from donation after cardiocirculatory death (DCD) donors is one of the options to avoid organ shortage in LTx. After extensive experimental research, clinical application of DCD donation is becoming wider. The results from most of the centers show at least equal survival rate compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 66 publications
(151 reference statements)
0
33
0
Order By: Relevance
“…Lungs are the only organs that do not require circulation to maintain the aerobic cellular metabolism because of the mechanism of passive diffusion across the alveolar membrane. Adequate gas exchange has been shown after 2 h of WIT in the absence of lung circulation, 28 which is why most programs recommend a WIT <150 minutes and a maximum preservation time <240 minutes. 9,17 Our protocol initially shortened these limits up to 120 minutes and 180 minutes, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Lungs are the only organs that do not require circulation to maintain the aerobic cellular metabolism because of the mechanism of passive diffusion across the alveolar membrane. Adequate gas exchange has been shown after 2 h of WIT in the absence of lung circulation, 28 which is why most programs recommend a WIT <150 minutes and a maximum preservation time <240 minutes. 9,17 Our protocol initially shortened these limits up to 120 minutes and 180 minutes, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, despite being a young non-smoker, our donor had a complicated past medical history which included direct and indirect injuries to the lungs: pulmonary embolism and cardiac diseases, respectively. Furthermore, he collapsed in a swimming pool and the bronchoscopic evaluation confirmed the presence of aspiration, which is considered a contraindication for the usage of lungs from DBD donors too [ 4 , 5 , 14 , 15 ]. The suitability of lungs from an uncontrolled DCD donor is established using stringent criteria, especially regarding ischemic time; however, the limit of tolerated ischemic time varies among different centres.…”
Section: Discussionmentioning
confidence: 99%
“…The International Society for Heart and Lung Transplantation (ISHLT) DCD working group recommended in 2015 six crucial time points in the DCD process ( Fig. 1) [5,20].…”
Section: Definition Of Donation After Circulatory Death Timingsmentioning
confidence: 99%
“…It was shown that universal identification of potential DCD donors could increase LTx activity by 50%, which would result in a virtual elimination of the waiting-list [7]. Although countries like the United Kingdom, Australia, Belgium and the Netherlands reached a high percentage of DCD donors, a continuous global underutilization is noticed [5,8,9]. In 2018, the OPTN reported that only 6.6% (n ¼ 169) of all LTx (n ¼ 2542) came from DCD, within Eurotransplant DCD utilization accounted for 5% (n ¼ 62) of all LTx in 2017 (n ¼ 1233) [10,11].…”
mentioning
confidence: 99%